Optimization of basic red 46 removal using chemically modified banana stalk - Nurul Sa'adah Mohamad Zaini (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
This research was conducted to study the feasibilty of using banana stalk as biosorbent for the removal of Basic Red 46 (BR 46) dye. The chemical pretreatments were applied to the biosorbent by using hydrochloric acid (HCl) and sodium hydroxide (NaOH). Batch biosorptions were conducted to investigate the effect of biosorbent dosage (1 to 9 g/L) and pH (4 to 12) of dye solutions on adsorption performance. The results revealed that treated biosorbent exhibited better biosorption performance than untreated biosorbent. Scanning Electron Microscope (SEM) proved that morphology surface of treated biosorbent high in porosity compared to untreated biosorbent. Response Surface Methodology (RSM) has been used in this study and optimum experimental conditions were found to be 8.40 g/L (HCl-treated biosorbent) and 7.40 g/L (NaOH-treated biosorbent) for biosorbent dosage and 9.20 (HCl-treated biosorbent) and 9.40 (NaOH-treated biosorbent) for pH.